Case study analysis concerning social accountability management success factors - Dragomir, Diana; Teleaba, Florian; Dragomir, Mihai (Technium Social Sciences Journal, 2020)
The article presents a case study dealing with two companies in Romania that have implemented social accountability management systems in accordance with the SA8000 standard and improved them over the course of almost a decade. The analysis is performed in the context of the need to formalize private sector approaches to corporate citizenship through CSR initiatives and frameworks. It involves a semi-structured interview in each of the companies and the use of the benchmarking tool to perform a comparison among them. The discussion is focused on identifying success factors conducive to each situation or overall, that could be disseminated as good practices to other companies interested in pursuing the same effort.